Manajemen Strategi Rekruitmen Kepala Madrasah Yang Responsif Gender di Lingkungan Kementerian Agama RI - Hesti Kusumaningrum; Kastolan Kastolan (Peneliti.net, 2022)
Achieving success in recruiting teachers and leaders is more than just filling job openings. It's about recruiting the best teachers and leaders, developing and retaining them. In the words of Nelson Mandela,